Minds at Play: Using an Online Protein Folding Game, FoldIt, To Support Student Learning about Protein Folding, Structure, and the Scientific Process - Rebecca Rashid Achterman (Journal of Microbiology & Biology Education, 2019)
Structure-function relationships of biological molecules are foundational to undergraduate biology education. In this article and supplemental information, an in-class activity is presented that uses a freely available online game to visualize the nature of chemical bonds as they relate to protein folding and structure. Activity questions and discussion guide students through a consideration of common structural elements as well as the nature of the scientific process. The activity was used in a lab section but could also work as a homework assignment. Student comments from a survey at the end of the course were overwhelmingly positive and indicated the activity helped them appreciate the complexity of protein folding as well as the scientific processes used to solve protein structures.